2017
DOI: 10.1073/pnas.1705129114
|View full text |Cite
|
Sign up to set email alerts
|

Atypical interactions of integrin α V β 8 with pro-TGF-β1

Abstract: Integrins α V β 6 and α V β 8 are specialized for recognizing pro-TGF-β and activating its growth factor by releasing it from the latency imposed by its surrounding prodomain. The integrin α V β 8 is atypical among integrins in lacking sites in its cytoplasmic domain for binding to actin cytoskeleton adaptors. Here, we examine α V β 8 for atypical binding to pro-TGF-β1. In contrast to α V β 6 , α V β 8 has a constitutive extended-closed conformation, and binding to pro-TGF-β1 does not stabilize the open confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 33 publications
3
55
0
Order By: Relevance
“…However, recent EM-based studies suggested that this simple assumption may not hold true, at least for some integrins. For example, it was shown that αVβ8 integrin assumed a constitutively extended conformation, regardless of the affinity states toward its physiological ligand, latent TGF-β (Wang et al, 2017;Minagawa et al, 2014). Furthermore, Springer and colleagues reported that the α5β1 integrin ectodomain rarely assumed the acutely bent conformation even in its resting (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent EM-based studies suggested that this simple assumption may not hold true, at least for some integrins. For example, it was shown that αVβ8 integrin assumed a constitutively extended conformation, regardless of the affinity states toward its physiological ligand, latent TGF-β (Wang et al, 2017;Minagawa et al, 2014). Furthermore, Springer and colleagues reported that the α5β1 integrin ectodomain rarely assumed the acutely bent conformation even in its resting (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Integrins α 4 β 1 , α 5 β 1 , and α V β 6 all appear to have bent-closed, extended-closed, and extended-open conformations. This conclusion is directly demonstrated for α 5 β 1 and α V β 6 by EM (10,11) and may be inferred for α 4 β 1 by the effects of Fabs that stabilize the closed, open, and extended states on affinity of soluble α 4 β 1 fragments for ligands and α 4 β 1 -dependent cell adhesion to specific ligand (6). We therefore interpret the increase in α Values are mean ± SD for one measurement each with Fn3 7-10 , Fn3 8-10 , and Fn3 9-10 , with the exception of the headpiece in Mg 2+ , for which Fn3 7-10 and Fn3 9-10 results could not be fit, and the fit ± fitting error is shown for Fn3 8-10 .…”
Section: Discussionmentioning
confidence: 56%
“…Overall, these results reveal major differences in the way in which important structural components in integrins, including the transmembrane/cytoplasmic domains and lower legs, regulate ligand-binding affinity by the integrin head. Recent studies on integrin α V β 8 also revealed only a four-to fivefold difference in affinity among clasped and unclasped ectodomain and headpiece forms (11). However, α V β 8 exists only in the closed conformation (11,14) and therefore is not comparable to α V β 6 , α 4 β 1 , or α 5 β 1 , all of which have both closed and open conformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations